Empowerment to Increase the Human Capital of Female Fishermen Through Non-Formal Education - Afriana, Wendra; Damanhuri, Didin S.; Taryono; Amanah, Siti (International Journal of Science and Society, 2024)
Fisherwomen, as agents of change, have an important role in developing a quality next generation in the economic and domestic fields. Their involvement in religious activities and training shows a significant impact in empowering and developing fishing communities. This research aims to analyze how the empowerment of female fishermen can be carried out through non-formal education and training to improve the quality of human capital. This research uses a qualitative approach with a gap analysis method. Data was collected through interviews and observations related to the women fishermen empowerment program. The research results show that female fishermen play an important role in developing human resources through religious and ethical education, with support from the Ministry of Religion and the Ministry of Maritime Affairs and Fisheries. Limited religious and social insight can be overcome through non-formal education, which emphasizes character-building and local wisdom. The importance of a holistic approach involving intellectual, emotional, and spiritual aspects (IQ, EQ, and SQ) is emphasized in the education and empowerment of female fishermen. Local wisdom and cultural values are key factors in encouraging social cohesion and the effectiveness of empowerment programs. This research suggests that empowering female fishermen must involve more than just increasing IQ, by utilizing technology and the internet to optimize their potential in developing fishing communities.